Incomplete CRAO: rare diagnosis and potential glaucoma mimicker - Hynes, Alexander (Canadian Journal of Optometry, 2023)
Many different ocular conditions can mimic glaucoma in causing retinal ganglion cell death and visual field loss. One subgroup of said ocular conditions includes retino vaso-occlusive events. There is a particularly under-appreciated and rare condition within this subgroup, the partial central retinal artery occlusion. Clinical presentation, prognosis, and systemic associations of partial CRAO will therefore be examined using a case as an example. Optical coherence tomography methods to distinguish between different etiologies behind retinal ganglion cell death will also be discussed using this case. These methods will be of use to clinicians in cases where previous ocular history is unable to be acquired.